Âşûrâ Günü’nde Aileye İkramda Bulunmaya Teşvik Eden Tevsi‘a Hadisinin Sened ve Metin Açısından Tahlili - Kazan, Tahsin (Çankırı Karatekin Üniversitesi, 2024)
Müslümanların din tasavvurunu şekillendiren temelde Kur’ân ve hadislerdir. Kur’ân’ın sıhhati noktasında bir kuşku bulunmamaktadır. Hadislerin tashih ve tadîfini belirlemek için birçok kıstâs bulunmakla birlikte öne çıkan kriter, sened ve metin tenkididir. Muhaddisler bir hadisi değerlendirirken öncelikle senedine bakmışlardır. Sened sağlam değilse metin tenkidine gidilmemiş senette yer alan râvilerinin durumuna bakarak rivâyete bir isim vermişlerdir. Muhaddislerin râviler hakkında farklı içtihatta bulunmalarının, hadislerin uygulanmasında az da olsa farklı sonuçlara yol açtığı bilinmektedir. Her toplumda sosyal hayatı şekillendiren ve gelenek haline gelmesini sağlayan bazı uygulamalar var olmuştur. Bu uygulamaları besleyen ve onlara dayanak oluşturan bazı hadislerin etkisi ise inkâr edilmez bir hakikattir. Günümüzde ‘Âşûrâ' geleneği bazı ülkelerde ve özellikle Türkiye’de yaygın bir şekilde sürdürülmekte, bu geleneğin oluşmasında ve devam etmesinde ise tevsi‘a hadisinin etkisi olduğu düşünülmektedir. Bu çalışmada ‘Âşûrâ’ gününde başta aile fertlerine ve insanlara yapılan ikramların sağlam bir delile dayanıp dayanmadığı, sened ve metin açısından tahlil edilecektir. Ayrıca bir haberin fazla tarikinin olmasının, rivâyete sıhhat hükmünü kazandırıp kazandırmayacağı de ele alınacaktır.

Analysis of the Hadith of Tawsi’a (Expansion) Which Encourages Giving Treats to the Family on the Day of Ashura in Terms of Sanad (the Chain of Narration) and Matn (Text) It is basically the Quran and hadiths that shape the religious perception of Muslims. There is no doubt about the authenticity of the Quran. Although there are many criteria to determine the correction of hadiths, the prominent criterion is the criticism of the chain of narration (sanad) and the text (matn). When evaluating a hadith, most of the scholars of hadith first examined its chain of narration. It is a known fact that some hadith scholars do not criticize the text if the narration is not reliable, and they give a name to the narration by looking at the status of the narrators in the narration. Also, it is seen that the different opinions among scholars regarding the narrators are known to lead to slightly different conclusions in the application of the hadiths. In every society, there have been certain practices that shape social life and become traditions. The impact of some hadiths that support these practices and provide a basis for them is an undeniable fact. Today, the tradition of Ashura is widely observed in some countries, particularly in Turkey, and it is believed that the influence of the hadith of tawsi’a (expansion) has played a role in the formation and continuation of this tradition. This study will analyze in terms of the chain of narration and the text whether giving treats to family members particularly and other people on the day of Ashura is based on solid evidence. In addition, the issue of whether having multiple chains of transmission for a narration enhances its authenticity will also be addressed.
Analysis of the Hadith of Tawsi’a (Expansion) Which Encourages Giving Treats to the Family on the Day of Ashura in Terms of Sanad (the Chain of Narration) and Matn (Text)
Keywords: Hadith; Hadis